Real time monitoring of capacitor degradation in industrial variable speed drives - Raqib, Abdurrahman (2022)
This thesis investigates a condition monitoring strategy suitable for use with monitoring the impedance of electrolytic capacitors in the DC-link of a motor drive, in contribution to the development of advanced intelligent variable speed drives.